Hallyu Stars in the Philippines: Effects of Brand and Endorser’s Credibility on Filipino Purchase Intention - Eunizer Aldrich A. Rono; Jean Paolo Lacap; Jeren B. Quipia; Albert John C. Paral; Mary Devine L. Sablas; Nicanor Jayson M. Coro (Jurnal the Messenger, 2024)
Introduction: There has been a notable rise in the popularity of K-pop endorsers within the landscape of Philippine advertising, influencing Filipino consumers' purchase intentions. Therefore, this study aims to examine the mediating effect of attitude toward a brand on the relationship between brand credibility, endorser credibility, and consumers' purchase intentions.